Sugarcane Breeding, Germplasm Development and Supporting Genetic Research in Argentina - Ostengo, Santiago (2021)
Sugar production from sugarcane is one of the oldest agro-industries in Argentina and plays an important role on economic and social activities in Tucumán, Jujuy and Salta Provinces, located at the Northwest region of the country. Sugarcane production features are different between Tucumán and, Salta and Jujuy (Northern provinces), for that reason different breeding programs are developed in each region. The present review summarizes the main characteristics of sugarcane breeding programs of Estación Experimental Agroindustrial Obispo Colombres (EEAOC) and Chacra Experimental Agrícola Santa Rosa (Chacra) that develop varieties for Tucumán and northern provinces, respectively. Breeding goals, history, germplasm collection, breeding methods, varieties currently grown in both productive areas, and molecular genetics and biotechnology supporting research are described. Efforts performed to develop sugarcane varieties adapted to diverse agro-ecological and management conditions have contributed to the profitability of industry as well as overcoming sanitary outbreaks. Improved varieties are key tools for the sugarcane production system, thus generating significant contributions for the socio-economic development of the region.